Peranan Lembaga Pengelola Zakat dalam Menanggulangi Pandemi Covid-19 - Alkaf, Syarifah Salsabila Yasmin Alkaf; Budiman, Mochammad Arif (P3M Politeknik Negeri Banjarmasin, 2023)
The Covid-19 pandemic has caused serious economic and non-economic impacts for all countries in the world. This research aims to explain the role of zakat management institutions in overcoming the impacts of the Covid-19 pandemic faced by the community. Two zakat management institutions, namely LAZISMU Banjar Regency and Kotakamal Indonesia Banjarbaru are the objects of research. This type of research is qualitative with a comparative approach. The results showed that both institutions implemented new strategies in fundraising during the pandemic, namely maximizing the use of technology and social media. Both institutions recorded an increase in the collection and distribution of funds. During the pandemic, fund distribution was carried out by suppressing the spread of the pandemic, providing education, and channeling social and economic assistance to affected communities.